Mongolias economic prospects resource-rich and landlocked between two giants. - Helble, Matthias; Hill, Hal; Magee, Declan (Asian Development Bank, 2020)
This book examines Mongolias recent economic development and outlines reforms that would help the country take advantage of its many opportunities.